Teaching under stress and fatigue: Can affect of the performance? - Gurdani Yogisutanti; Linda Hotmaida; Yayang Gustiani; Sri Wahyuni Panjaitan; Suhat Suhat (Al-Sihah : The Public Health Science Journal, 2020)
Workload, work stress, work fatigue, and performance are important variables in an organization, which must be well organized so that the organization can run well and succeed. The purpose of this study was to determine the relationship between workload, work stress, work fatigue, and teacher performance. The research design used was cross-sectional in 38 teachers of SMP Negeri 3 Bandung city taken in total sampling. The instrument was adopted from previous studies which have been validity and reliability tested. The results showed all teachers have moderate workloads, experience mild stress, and poor performance. Most respondents experienced work fatigue (76.3%). Statistical tests using the Spearman Rank Correlation Test and Product Moment concluded that there was a relationship between workload, work stress, and teacher performance. There is a relationship between work stress, work fatigue, and teacher performance and also the relationship between workload and teacher performance. There is a negative relationship between workload and performance, neither is the relationship between work stress, work fatigue, and teacher performance. Suggestion for SMPN 3 Bandung city is to organize workshops to improve teacher performance, and giving refreshing once a year to prevent work stress.